DIPG-42. CAN WE CHANGE THE LANDSCAPE OF PEDIATRIC DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG)? FIRST DEMONSTRATION OF CLINICAL AND RADIOGRAPHIC RESPONSE IN A PEDIATRIC H3-K27M MUTATED DIPG TO THE DRD2-ANTAGONIST ONC201. Issue 2 (22nd June 2018) - Hall, Matthew; Odia, Yazmin; Allen, Joshua; Tarapore, Rohinton; Khatib, Ziad; Maher, Ossama; Niazi, Toba; Daghistani, Doured; Schalop, Lee; Chi, Andrew; Oster, Wolfgang; Mehta, Minesh
Abstract: INTRODUCTION: DIPG is uniformly fatal, with a median survival of 8–9 months. We report the first pediatric patient with H3-K27M mutated DIPG treated with conventional radiotherapy and the small molecule DRD2-antagonist ONC201, with a sustained radiographic and clinical response after 8 months of therapy. CASE: A 10-year-old female presented with House-Brackmann Grade IV facial palsy and unilateral hearing loss in 2/2017. MRI demonstrated a 2.3x2.1x2.7 cm medullopontine tumor. Stereotactic biopsy confirmed H3-K27M mutated diffuse midline glioma. She completed intensity-modulated radiotherapy (59.4 Gy/33 fractions) in 5/2017. MR imaging 1-month post-radiotherapy demonstrated reduction in tumor volume (2.0x1.9x2.7 cm) with persistent Grade IV facial palsy.The patient began oral ONC201 (500 mg weekly) as a single agent in 6/2017 on an IRB-approved compassionate use protocol with MRI every 2 months. ONC201 is a first-in-class DRD2-antagonist that crosses the blood-brain barrier and has shown efficacy in high grade glioma preclinical models through a p53-independent mechanism. Tumor volume sequentially decreased by 30.6, 33.2, and 41.9% over the next three MRIs, reaching 1.8x1.7x1.9 cm at 6 months from initiation of ONC201. Ipsilateral hearing was restored and the facial palsy improved to House-Brackmann Grade I by 16 weeks after starting ONC201. CONCLUSION: The patient remains clinically improved and without adverse events 8 months after starting ONC201 and 11 months from diagnosis. This case provides initial proof-of-concept for this novel agent targeting H3-K27M DIPG. Phase II trials are ongoing to evaluate the efficacy of ONC201 in adult and pediatric patients with H3-K27M gliomas.